Analysis of Product Knowledge and Shopping Experience on Intention to Buy an Oppo Smartphone at Shopee with Perceptions of Risk - Irma Dwi Kusuma; Tri Kartika Pertiwi; Akhmad Fauzi (LPPM of NAROTAMA UNIVERSITY, 2021)
SMARTPHONE is considered a device that helps in everyday life, especially during the Covid-19 pandemic. One of the smartphones that have the largest market share in Indonesia is Oppo, but amid the sharp increase in smartphone online sales, Oppo's online sales are not showing an increase. Even though currently, there are various types of online shopping destinations, one of which is the marketplace, which provides shopping convenience and complete information about products. This is expected to form a good shopping experience and product knowledge to reduce consumer risk perceptions about creating online purchase intentions, so the purpose of this study is to analyze the effect of product knowledge and shopping experience on purchase intention with risk perception as an intervening variable. This research is quantitative. Respondents are residents of Surabaya who have made purchases at Shopee. The sample used was 110 people. The withdrawal used the snowball sampling technique. The research instrument was a questionnaire, then the data obtained were processed by PLS-SEM. The results show that product knowledge contributes to purchase intention. The shopping experience does not contribute to purchase intentions. Product knowledge and shopping experience contribute to risk perception. Meanwhile, the indirect relationship shows that risk perception is proven to mediate the relationship between product knowledge and shopping experience variables with purchase intention.